Kerangka Konseptual Terintegrasi yang Menghubungkan Sifat Mekanik dan Mekanisme Kegagalan pada Material Teknik - Lalak Indiyono (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Engineering materials failure remains a critical issue in structural and manufacturing applications, where unexpected fracture can lead to severe safety and economic consequences. Conventional approaches often address mechanical properties, stress analysis, and fracture behavior as separate topics, which may result in fragmented interpretations of failure mechanisms. However, material failure typically emerges from interactions between global mechanical response, stress localization, microstructural defects, and fracture initiation. This paper proposes an integrated conceptual framework that systematically links mechanical properties with failure mechanisms in engineering materials. The framework synthesizes key concepts from strength of materials and fracture mechanics to describe failure as a sequential and interconnected process, starting from applied loading and global stress–strain response, followed by stress concentration, defect activation, and crack initiation. By explicitly addressing the transition from macroscopic mechanical behavior to localized damage processes, the framework clarifies the role of defect sensitivity and stress localization in governing failure modes.